Generalized Growth of Special Monogenic Functions. (1st April 2014) - Kumar, Susheel
Abstract : We study the generalized growth of special monogenic functions. The characterizations of generalized order, generalized lower order, generalized type, and generalized lower type of special monogenic functions have been obtained in terms of their Taylor's series coefficients.